Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Loyal - Mega Naliyah Syahfitri; Danang Kusnanto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The study aims to find out, explain, and analyze a phenomenon about the influence of service quality on customer satisfaction that has an impact on customer loyalty (case study of IndiHome in Karawang district during the Covid-19 pandemic). This research was conducted using descriptive and verification methods, namely knowing, explaining, analyzing and testing hypotheses, as well as making conclusions and suggestions. The sample was carried out using incidental sampling with a sample of 316 respondents from an average population of 1,494 customers each month. The results of this study indicate that the Quality of Service at IndiHome, Karawang Regency, is in good criteria. IndiHome Customer Satisfaction in Karawang Regency is in the satisfied criteria. IndiHome Customer Loyalty in Karawang Regency is in the loyal criteria. There is a direct and significant effect between service quality and customer satisfaction by 64%. There is a direct and significant effect between customer satisfaction and customer loyalty of 68.6%. There is an indirect effect of service quality on customer loyalty through customer satisfaction of 66.24%.